La justicia de la inmigración: algunos modelos argumentativos = The justice of immigration: some models of argumentation - Loewe, Daniel (Civitas - Revista de Ciências Sociais)
The paper analyzes the normative relationship between (a) communitarian, (b) liberal nationalist, (c) libertarian and (d) liberal egalitarian theoretical argumentative structures, and the issue of immigration. According to the defended argument, the limits on immigration that these theories stand up for as beeing reasonable are difficult to sustain